An Assessment Of Osteoporosis Condition And Knowledge Among Warfarin Users At A Hospital In The Northern Region Of Peninsular Malaysia - Abdulameer, Aseel Hadi (2017)
Osteoporosis is a chronic disease that has a complex relation with patients using warfarin. In order to provide optimal management of osteoporosis, there is a need to advice patients about the usage of warfarin. A clinical part involved casecontrol study of a convenient sample of 270 subjects (controls and patients) recruited to assess the bone health status by measuring the bone mineral density (BMD) using quantitative ultrasound scan (QUS) as well as to evaluate their osteoporosis knowledge (OKT). The result of QUS showed that the prevalence of normal BMD, osteopenia, and osteoporosis were 23.3%, 53.7%, 23% respectively.